(untitled) (Acta Scientiarum. Education, 2015)
In recent years, Professional Education has been a widespread theme in Brazil. In a political and educational scenario marked by flexible accumulation and by the neoliberal ideology, actions and programs aimed at teacher training for professional education are discussed within the context of the National Education Bases and Guidelines Law. This paper analyzes the impact of the Special Program for Teacher Training on the teaching praxis of the middle-level professional education offered by the State Center of Technological Education Paula Souza during 2010. The analysis of the research data based on the dialectical and historical materialism of Marx and Engels shows that the multiple facets of policies for initial and continuing education of teachers are conducted through liberalization, pluralization and indiscriminate expansion of training institutions and ineffective courses. The Special Program for Teacher Training reveals itself as part of the framework of isolated educational policies that do not face the problem but insist on postponing it. Amid intense changes, they foreground discontinuity, the urgent character and the predominance of the quantitative aspect over the qualitative one.